Realities of Teachers’ Professional Development in Community Campuses of Tribhuvan University - Ghimire, Nani Babu (NUTA Journal, 2019)
Teacher professional development (TPD) is the modern aspect of teaching learning process. To do effective teaching, the teacher should be trained, excellent as well as up-date according to the change of time. The main purpose of this paper is to explore realities of the teachers’ professional development of the teachers in community campuses of Tribhuvan University (TU). There is great importance of TPD in the teachers of the community campuses since it helps the teacher to develop various kinds of professional skills, knowledge, new techniques and modern technology of teaching. Similarly, there is the great role of TU for the TPD of the teachers of community campuses. As the affiliation university it should organize subject wise teachers’ training time and again. Similarly, it should hold seminar, workshop and conference on the burning issues of teaching and learning. Teachers’ professional development is the demand of the present time and promoting teachers’ capacity is the most important aspect of the quality education. This article is based on the theme of the mini research which is approved by University Grants Commission (UGC) Nepal.